SPIRITUALITAS LUKISAN AMANG RAHMAN JUBAIR - Hajriansyah, Hajriansyah (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2017)
This study focusedon the spirituality values in paintingsof Amang Rahman Jubair, particularly from the perspective of the sufi aesthetics. Amang Rahman (1931-2001) was an Indonesian painter which has a deeply awareness of God's presence, and have a concept of art which he called Jamal, Kamal and Jalal?embodied by the sweat, blood and tears, which means sacrifice, devotion and love to the Creator and His creatures. Forms of this study is a qualitative field research by using descriptive analytical method and approach of Sufi Aesthetics. The sources is the family and closest-friends of Amang Rahman, a few paintings and journalistic articles and Indonesian art critics writings of his works. This study suggests that Amang Rahman is a sufi in a modern world. Experiences and attitudes totality of his life proving his devotion to both the art and life itself intact. In the works of his art reflected awareness of space and the cosmos that represents nature imajinal ('alam al-khayal), traditions and symbols of Sufism.